Value added tax : - Schenk, Alan (Cambridge University Press, 2007)
This book integrates legal, economic, and administrative materials about value added tax. Its principal purpose is to provide comprehensive teaching tools - laws, cases, analytical exercises, and questions drawn from the experience of countries and organizations from all areas of the world. It also serves as a resource for tax practitioners and government officials that must grapple with issues under their VAT or their prospective VAT. The comparative presentation of this volume offers an analysis of policy issues relating to tax structure and tax base as well as insights into how cases arising out of VAT disputes have been resolved. In the new edition, the authors have expanded the coverage to include new VAT related developments in Europe, Asia, Africa and Australia. A new chapter on financial services has been added as well as an analysis of significant new cases